SYSTEMATIC REVIEW ON ARTIFICIAL INTELLIGENCE(AI) ENABLED INSURANCE SECTOR - Yao Di; Bamini KPD Balakrishnan, (Malaysian Journal of Business and Economics (MJBE), 2025)
This study looks into the application of AI technology in the insurance industry, Through a systematic literature review, the study initially sorts out the status and progress of existing studies on the application of AI based on risk assessment, claims processing, customer service, and product personalization. Followed by additional analysis on the relevance of the data in terms of content analysis, the role and potential challenges of AI technology in enhancing operational efficiency, improving customer experience, and strengthening risk management. The results of the review showed that the wide application of AI not only improves the intelligence of insurance but also provides support for the long-term competitiveness of the industry. Eventually the study concludes with the future of AI applications in insurance and suggests solutions in line with data privacy, technical barriers, and algorithmic bias.